2021
DOI: 10.1136/bcr-2020-239456
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary metastases of Hürthle cell carcinoma of the thyroid

Abstract: An 85-year-old man was referred to endocrinology following the discovery of an incidental pituitary mass on cranial imaging which was thought to be a non-functioning adenoma during an admission with headaches, lethargy, confusion and hyponatraemia. He had a history of Hürthle cell carcinoma of the thyroid treated with total thyroidectomy, ablative radioiodine therapy and thyroxine replacement. Subsequently, he developed metastatic spread to the neck, lungs and skeleton. About 9 months later, the patient had de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The results of the quality assessment of the eligible studies are shown in Supplementary Material 2 ( www.wjon.org ) [ 5 , 9 , 10 , 15 - 36 ]. Twenty studies had moderate quality, while the remaining five were rated low.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the quality assessment of the eligible studies are shown in Supplementary Material 2 ( www.wjon.org ) [ 5 , 9 , 10 , 15 - 36 ]. Twenty studies had moderate quality, while the remaining five were rated low.…”
Section: Resultsmentioning
confidence: 99%
“…PM from differentiated thyroid cancer (DTC) is extremely uncommon and represents a rare site for metastases [ 5 - 8 ]. Less than 30 cases have been reported in the literature [ 9 , 10 ]. Some reports have indicated differences in PM manifestations in the DTC setting compared to non-thyroid cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 16 Metastasis to the brain is very rare in all subtypes of metastatic thyroid carcinoma; to our knowledge, only 3 cases of HCC metastasis to the central nervous system have been reported. 3 McWilliams et al 15 found that median survival for patients with metastatic thyroid carcinoma to the brain was 20.8 months for patients who had undergone partial or gross-total resection, but this was further reduced to only 8.3 months when evaluating patients with carcinomas of follicular cell origin. Patients who did not undergo any resection had a median survival of 2.7 months.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Hürthle cell carcinoma typically metastasizes to the lung and bones, with brain metastases (BMs) being uncommon. 2 However, rare cases of pituitary metastases, 3 skull metastases, 4 single choroid plexus metastasis, 5 and cerebral metastasis 6 of HCC have been reported in the literature. Patients with distal DTC metastasis have poor outcomes, and those with BM have a worse overall survival, ranging from 7.1 to 33 months.…”
mentioning
confidence: 99%